Public Debt, Global Governance and Economic Dynamism 2013
DOI: 10.1007/978-88-470-5331-1_20
|View full text |Cite
|
Sign up to set email alerts
|

EMU Sovereign Spreads and Macroeconomic News

Abstract: We investigate the relationship between macroeconomic news and sovereign spreads in the euro area at weekly frequency. Our focus lies in the role played by macroeconomic announcements. To this aim we augment a standard GARCH model with a synthetic measure for macroeconomic surprises obtained by aggregating deviations between data releases and market expectations on a set of indicators chosen for being closely watched by economic analysts and financial operators. We find that the dissemination of macroeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In the brackets, we express the number of better-than-expected news announcements, the number of worse-than-expected news announcements, and the announcements correctly anticipated by the market consensus. 6 Complexity sample to investigate the overall reaction of the CDS spread to macro news, while in Section 4.3, we take the average in each region so that we can analyse the differences in the reaction between the three regions) abnormal spread changes (CAASC):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the brackets, we express the number of better-than-expected news announcements, the number of worse-than-expected news announcements, and the announcements correctly anticipated by the market consensus. 6 Complexity sample to investigate the overall reaction of the CDS spread to macro news, while in Section 4.3, we take the average in each region so that we can analyse the differences in the reaction between the three regions) abnormal spread changes (CAASC):…”
Section: Methodsmentioning
confidence: 99%
“…Bond prices are investigated by Beetsma et al [4] who found that bond yield spreads are deemed to be volatile during announcement speeches with consistent spillover effects. Andritzky et al [5], Arru et al [6], and Kurov and Stan [7] modeled the bond volatilities in emerging markets and the US bond market. Vrugt [8] tested whether macroeconomic announcements play a role in the determination of conditional means, variances, and covariances in the stock and bond markets.…”
Section: Introductionmentioning
confidence: 99%